Serum Uric Acid as a Biomarker in Patients Admitted with Acute Exacerbation of Chronic Obstructive Pulmonary Disease to a Tertiary Hospital, Kerala - Mervin K. Soman; Jesin Kumar Chakkamadathil; Hafseena Noorayingarath; A. Gayathri Lal (Journal of Advanced Lung Health)
Background: Chronic obstructive pulmonary disease (COPD) is a highly prevalent and debilitating condition worldwide, imposing significant economic and social burdens on societies. Serum uric acid contributes to inflammation and is often used a biomarker. Aims and Objectives: This study aims to assess the potential role of serum uric acid as a cost-effective biomarker in hospitalized patients experiencing acute exacerbation of COPD. Additionally, it aims to investigate the relationship between the severity of airflow obstruction and serum uric acid levels in patients with COPD. Materials and Methods: The study design is a prospective cohort study involving 144 COPD patients admitted for acute exacerbation, excluding those with concurrent chronic comorbidities or receiving medications known to substantially elevate uric acid levels. Results: Our findings demonstrate elevated serum uric acid levels in patients with advanced-stage COPD and severe airflow obstruction. Furthermore, patients with higher levels of serum uric acid exhibit poorer prognosis compared to those with lower levels in COPD. Conclusion: Serum uric acid can serve as a valuable biomarker to prognosticate COPD patients and assess disease severity in patient admitted with exacerbations.